THEORETICAL FOUNDATIONS OF COMPETITIVENESS MANAGEMENT OF HEALTH CARE INSTITUTIONS - Yuriy Safonov; Viktoriia Borshch; Oleksandr Rogachevskyi (Baltic Journal of Economic Studies, 2022)
Increasing the competitiveness of health care institutions is an urgent issue for health care in the new funding environment. The purpose of this work is to analyze the existing tools for competitiveness management in the healthcare sector. The problems of competitiveness management development are investigated. State regulation, political dynamics, changing socio-demographic characteristics and constant technological development cause significant changes in the healthcare sector, but despite this, state restrictions, conservatism of Ukrainian healthcare and lack of management specialists are the main problems of Ukrainian healthcare. This necessitates the use of the principles of competitiveness management of modern health care institutions. The main methodological approach used in the work is a review of literature sources. The analysis of scientific literature revealed the absence of unified methodological approaches to measuring competitiveness, and many of the proposed methods do not take into account the specifics of the health care system, as well as the areas of activity of the medical organization. The existing models of competitiveness management tools differ from each other, and their use is conditioned by many factors. The role and impact of competition in the healthcare sector is considered separately. The theoretical basis of the study is a systematic approach to understanding the relationship between different levels of health care. Important conceptual issues of measuring competition in healthcare, including S.W.O.T. analysis, competitive advantages, human resources assessment, benchmarking, etc. are considered. The results of this study form the methodological and practical basis for improving the competitiveness management system of health care institutions in Ukraine, which operate in difficult socio-economic conditions.